2021
DOI: 10.1016/j.cjco.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Safety of Sacubitril/Valsartan in Women and Men With Heart Failure and Reduced Ejection Fraction: A Meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(116 reference statements)
1
8
0
Order By: Relevance
“…This high reduction in real-world setting (by comparison with ~ 21% vs . enalapril in the pivotal trial) 1 , is in line with previous reports 5 , 13 , 14 . In addition, real-world patients exhibited an improvement in NYHA class and a decreased use of most medications for HF and other relevant concomitant pharmaceutical therapies following treatment initiation.…”
Section: Discussionsupporting
confidence: 91%
“…This high reduction in real-world setting (by comparison with ~ 21% vs . enalapril in the pivotal trial) 1 , is in line with previous reports 5 , 13 , 14 . In addition, real-world patients exhibited an improvement in NYHA class and a decreased use of most medications for HF and other relevant concomitant pharmaceutical therapies following treatment initiation.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a recent meta‐analysis of cohort studies assessed sex‐specific data on major adverse outcomes and long‐term safety in 8981 patients treated with S/V. AEs were infrequent in both men and women and comparable with the findings of the pivotal trials, indicating that the safety of S/V can be replicated outside the clinical trial context 56 …”
Section: Safety and Tolerability In And Outside Clinical Trialsmentioning
confidence: 86%
“…AEs were infrequent in both men and women and comparable with the findings of the pivotal trials, indicating that the safety of S/V can be replicated outside the clinical trial context. 56…”
Section: Safety and Tolerability In And Outside Clinical Trialsmentioning
confidence: 99%
“…Furthermore, in HFpEF patients, women responded to treatment with ARNI at higher LVEF ranges than men [107]. The different efficacy in women and men was justified because postmenopausal women had greater visceral adipose tissue with increased neprilysin activity and lower NO synthases, microvascular inflammation, and bradykinin production [108]. However, a meta-analysis found that the safety profile was similar in both sexes in patients treated with ACEIs [109].…”
Section: Sandgds and Pharmacologic Therapy In Hfmentioning
confidence: 99%